Accountability Analysis With The Application Of Psak 112 In The Financial Statements Of Cash Waqf In Madura: Analisis Akuntabilitas Dengan Penerapan Psak 112 Pada Laporan Keuangan Wakf Tunai Di Madura - Wilantini, Cici’; Handayani, Sri; Abidin, Zainal (Universitas Muhammadiyah Sidoarjo, 2023)
The importance of accountability financial reports is a form of accountability from waqf assets entrusted by the wakif to an institution/agency that became nadzhir. The better the financial reports are made, the more trust will increase from the public and vice versa. PSAK 112 regarding waqf accounting can help nadzhir parties to prepare better financial reports of waqf assets. This research uses a qualitative descriptive type approach. The research locations are LAZISMU Pamekasan and KSPPS Nuri East Java. Sources of data in the form of observations, interviews and documentation. The results of the research are; Accountability from LAZISMU Pamekasan and KSPPS Nuri East Java has worked in accordance with the indicators and forming factors of financial report accountability. The application of PSAK 112 at LAZISMU Pamekasan has a conformity of 35% and the remaining 65% still needs to be improved. Whereas in KSPPS Nuri East Java it has a suitability of 41% and the remaining 59% still needs to be fixed again. This means that the financial statements of cash waqf funds issued by LAZISMU Pamekasan and KSPPS Nuri East Java are still lacking from the financial components commonly made by waqf institutions according to PSAK 112. At LAZISMU Pamekasan and KSPPS Nuri East Java there has been no instruction from the leadership to use PSAK 112 and there is no concrete socialization from the authorities